Pengaruh Self-Compassion terhadap Compassion Fatigue pada Perawat Hemodialisis - Prayogo, Maulana; Ariana, Atika Dian (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
Compassion fatigue is the exhaustion experienced by nurses in response to stress resulting from exposure to the pain and trauma of patients. The job characteristics of hemodialysis nurses place them at risk of compassion fatigue. The purpose of this research is to examine whether self-compassion influences compassion fatigue in hemodialysis nurses . This study was conducted on 73 hemodialysis nurses. The instruments used were the Self-Compassion Scale by Neff and the Professional Quality of Life Scale version 5 by Stamm. Data were analyzed using simple linear regression analysis for two aspects of compassion fatigue: burnout and secondary traumatic stress. The results of the study indicate that self-compassion has a significant negative impact on burnout and secondary traumatic stress. In other words, high self-compassion can predict low levels of burnout and secondary traumatic stress among hemodialysis nurses.